Automated vehicles and behavioural adaptation in Canada. (October 2017) - Robertson, Robyn D.; Meister, Shawna R.; Vanlaar, Ward G.M.; Mainegra Hing, Marisela
Abstract: The current tests of automated vehicles (AVs) with human back-up drivers and opt-into a self-driving car raise important questions regarding public awareness of the limitations of these vehicles. Road safety can be greatly improved by focusing on the often-overlooked intersection between driver behaviour and the use of new technologies. This paper presents the extent to which Canadian drivers self-reported how they would adapt their behaviour if using limited self-driving vehicles (LSDVs). An online survey and focus groups were conducted to explore the knowledge, attitudes, perceptions and behaviours of Canadians in relation to AVs. It was found that many drivers believed they would not need to pay attention to the road environment when using LSDVs, and that some of them would modify or adapt their behaviour in negative ways that would undermine safety objectives. These results provide insight useful to shape educational strategies, government policies, and tactics to help ensure the safety benefits that are highly expected of AVs actually materialize.